Pd-loaded In2O3 nanowire-like network synthesized using carbon nanotube templates for enhancing NO2 sensing performance. Issue 38 (27th March 2015) - Huang, Mingqi; Cui, Zhenduo; Yang, Xianjin; Zhu, Shengli; Li, Zhaoyang; Liang, Yanqin
Abstract : Pd–In2 O3 nanowire-like network sensor with characteristic response curve has potential application in preparing multi-functional gas sensors. Abstract : Pd-loaded In2 O3 nanowire (NW)-like networks were synthesized via electroless plating using carbon nanotubes (CNTs) as templates, followed by oxidation and removal of the CNTs at 550 °C. Palladium (Pd) was introduced to activate the surface of the CNTs for subsequent plating. Before calcination, Pd was loaded onto In2 O3 . The as-synthesized Pd-loaded In2 O3 replicated the structure of the CNTs, forming a porous NW-like network with a very large specific surface area. Furthermore, the NO2 gas sensing properties of the Pd-loaded In2 O3 NW-like network, porous Pd–In2 O3 and porous unloaded-In2 O3 were investigated. The results demonstrated that the Pd–In2 O3 NW-like network exhibits superior sensitivity with short response and recovery times, and demonstrates a significant response when exposed to NO2 at concentrations as low as 5 ppm at a temperature of 110 °C. A synergy of electric and chemical effects has been proposed to explain the gas sensing enhancement.